Student-Centred Learning in Higher Education: Exploring Indonesian English Language Lecturers’ Perception - Hidayatullah Yunus; Muhammad Ridha Anugrah Latief (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This study explores the perception of Indonesian English language lecturers in implementing Student-Centred Learning (SCL) in Indonesian higher education. One-way teaching method still occurs and needs to be shifted to two-way interactive teaching method or active learning to develop student engagement in learning activities, and SCL is considered as one of the approaches to develop student engagement. The focus of this study is more on the perception of three English language lecturers towards SCL implementation. This is to consider that their roles are essential in delivering the materials as their responsibility is to facilitate and to drive the learning activity, especially in teaching English as a Foreign Language (EFL) in Indonesian higher education. This research adopted qualitative study by conducting in-depth semi-structured interviews as the method for a small number of English language lecturer participants, and grounded theory was used as the analytical method enabling the presentation of lecturer perception from their context. Findings revealed that the three lecturers had an adequate understanding of the concept of SCL, and they thought implementing SCL is useful and valuable to develop students’ engagement with learning activities and to improve lecturers’ teaching practice even though there are still some challenges that need to be considered. The findings also showed how the participants encountered the challenges and the personal strategies that they saw as effective to be applied. This study suggests it is worth reconsidering the possibilities of valuable English language lecturers’ perception towards SCL implementation in Indonesian higher education.